Gelcast zirconia ceramics for dental applications combining high strength and high translucency. Issue 6 (24th February 2022) - Kastyl, Jaroslav; Stastny, Premysl; Chlup, Zdenek; Song, Lu; Scasnovic, Erik; Trunec, Martin
Abstract: Tetragonal zirconia polycrystals (TZP) represent a favorite material for monolithic ceramic dental restorations. However, all approaches employed so far to improve the translucency of dental zirconia ceramics are accompanied by a significant decline in strength. In this investigation, we developed dental 3Y‐TZP ceramics that can provide excellent strength combined with enhanced translucency. The machinable tetragonal zirconia discs and blocks were prepared from fine mesostructured zirconia particles stabilized with 3 mol% of yttria using the gelcasting method. Zirconia ceramics with an average biaxial strength of 1184 MPa and translucency of 41.1% for a 1 mm thick sample were obtained. Due to its unique microstructure, this tetragonal ceramic provided a favorable combination of high translucency comparable to the high‐translucent, tetragonal/cubic 4Y‐TZP and very high strength achievable only in the pure tetragonal 3Y‐TZP. The applicability and resistance to low‐temperature degradation of the new dental ceramics was demonstrated. Abstract : In this investigation, we developed dental 3Y‐TZP ceramics that can provide excellent strength combined with enhanced translucency. The CAD/CAM tetragonal zirconia discs and blocks were prepared from fine mesostructured zirconia particles stabilized with 3 mol% of yttria using the gelcasting method. Zirconia ceramics with an average biaxial strength of 1184 MPa and translucency of 41.1% for a 1 mm thick sample were obtained. Newly developed 3Y‐TZP ceramic provided a favorable combination of high translucency comparable to the high‐translucent, tetragonal/cubic 4Y‐TZP and very high strength achievable only in the pure tetragonal 3Y‐TZP. The applicability and resistance to low‐temperature degradation (LTD) of the new dental ceramics was demonstrated